Push-out bond strength of root-end filling materials - Vivan, Rodrigo Ricci; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Bosso-Martelo, Roberta [UNESP]; Costa, Bernardo Cesar [UNESP]; Duarte, Marco Antonio Hungaro; Tanomaru-Filho, Mário [UNESP] (FapUNIFESP (SciELO), 2016)
The aim of this study was to evaluate the bond strength of root-end filling materials. Forty 2-mm-thick slices were obtained from human single-rooted teeth. After root canal preparation using a 1.5 mm diameter cylindrical drill, the dentinal walls were prepared by diamond ultrasonic tip (CVD T0F-2). The specimens were divided according the material (n=10): MTA Angelus (MTAA), MTA Sealer (MTAS, experimental), Sealer 26 (S26) and zinc oxide and eugenol cement (ZOE). The push-out test was performed in a mechanical test machine (EMIC DL 2000) at 1 mm/min speed. The failure type was evaluated by stereomicroscopy. The results were subjected to ANOVA and Tukey test, at 5% significance level. MTAA (19.18 MPa), MTAS (19.13 MPa) and S26 (15.91 MPa) showed higher bond strength (p<0.05). ZOE (9.50 MPa) showed the least bond strength values (p<0.05). Adhesive failure was prevalent in all groups, except for ZOE, which showed mixed failures. It was concluded that root-end filling materials MTA Angelus, MTA Sealer and Sealer 26 showed higher bond strength to dentinal walls than zinc oxide and eugenol cement after retrograde preparation.
Keywords: Bond strength; Mineral trioxide aggregate; Push-out; Rootend filling material